2018
DOI: 10.1016/j.freeradbiomed.2018.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in the death of steatotic WIF-B9 hepatocytes co-exposed to benzo[a]pyrene and ethanol: a possible key role for xenobiotic metabolism and nitric oxide

Abstract: We previously demonstrated that co-exposing pre-steatotic hepatocytes to benzo[a]pyrene (B[a]P), a carcinogenic environmental pollutant, and ethanol, favored cell death. Here, the intracellular mechanisms underlying this toxicity were studied. Steatotic WIF-B9 hepatocytes, obtained by a 48hsupplementation with fatty acids, were then exposed to B[a]P/ethanol (10 nM/5 mM, respectively) for 5 days. Nitric oxide (NO) was demonstrated to be a pivotal player in the cell death caused by the coexposure in steatotic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 96 publications
2
12
0
Order By: Relevance
“…Xenobiotic detoxification metabolism consists of three phases. The phase I enzymes such as cytochrome P450 family 1 subfamily A member 1 (CYP1A1) and cytochrome P450 family 1 subfamily B member 1 (CYP1B1) introduce oxygen molecules to xenobiotic compounds [ 10 ]. The converted compounds are then conjugated to glutathione (GSH), sulfate, or glucuronic acid by phase II enzymes such as glutathione S-transferase alpha 1 (GSTA1) and glutathione S-transferase pi 1 (GSTP1).…”
Section: Introductionmentioning
confidence: 99%
“…Xenobiotic detoxification metabolism consists of three phases. The phase I enzymes such as cytochrome P450 family 1 subfamily A member 1 (CYP1A1) and cytochrome P450 family 1 subfamily B member 1 (CYP1B1) introduce oxygen molecules to xenobiotic compounds [ 10 ]. The converted compounds are then conjugated to glutathione (GSH), sulfate, or glucuronic acid by phase II enzymes such as glutathione S-transferase alpha 1 (GSTA1) and glutathione S-transferase pi 1 (GSTP1).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent investigations of different experimental models of MAFLD suggested that benzo[a]pyrene exposure might even further aggravate the progression of steatosis to steatohepatitis induced by ethanol [176,[213][214][215]. Potential mechanisms involved in such progression include overproduction of ROS and nitric oxide [176,214], mitochondrial dysfunction [176], increased expression of proinflammatory cytokines [213] and plasma membrane remodeling [215].…”
Section: Ethanolmentioning
confidence: 99%
“…For instance, benzo(a)pyrene (BP) can promote ROS production in liver cells both in vitro [24,25] and in vivo [26], leading to oxidative damages such as lipid peroxidation in cultured liver cells [27,28] or in mice liver [29], as well as DNA oxidation in hepatocytes [30] or in rat liver [31]. Those oxidative damages were demonstrated to be responsible for cell death in liver [27,28,32,33]. Pyrene (PYR) can also trigger ROS production in hepatocytes along with a decrease in the expression of antioxidant enzymes, thus leading to a loss of viability [34].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress measurement in hepatocytes ROS production. Intracellular ROS production was evaluated using dihydroethidium (DHE), as previously described[33]. Briefly, after treatment by hepatocyte-derived EVs, recipient cells were incubated with 25 μM DHE for 1 h at 37°C.…”
mentioning
confidence: 99%